2021
DOI: 10.3389/fpls.2021.756300
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Flavonoids in the Petals of Freesia and Prediction of Four Novel Transcription Factors Involving in Freesia Flavonoid Pathway

Abstract: Freesia hybrida is rich in flower colors with beautiful flower shapes and pleasant aroma. Flavonoids are vital to the color formation of its flowers. In this study, five Freesia cultivars with different flower colors were used to study on the level of accumulation of their flavonoids and expression of flavonoid-related genes and further explore new novel transcription factor (TF). Ultra-high-performance liquid chromatography and VION ion mobility quadrupole time-of-flight mass spectrometer (UPLC-Q-TOF-MS) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Additionally, the WD40 protein often forms transcriptional complexes with MYB and bHLH to regulate anthocyanin synthesis. Notably, WRKY transcription factors have been found to regulate anthocyanin production in Freesia hybrida , apples, and pears [ 28 , 29 , 30 , 31 ]. In P. mume , gene families encompassing R2R3-MYB, bHLH, WD40, and WRKY have been identified and systematically studied [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the WD40 protein often forms transcriptional complexes with MYB and bHLH to regulate anthocyanin synthesis. Notably, WRKY transcription factors have been found to regulate anthocyanin production in Freesia hybrida , apples, and pears [ 28 , 29 , 30 , 31 ]. In P. mume , gene families encompassing R2R3-MYB, bHLH, WD40, and WRKY have been identified and systematically studied [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Co-expression-network prediction and cis-element analysis with the promoters of flavonoid biosynthesis-related structural genes suggested that WRKY and AP2 TFs may play vital roles in regulating flavonoid biosynthesis [ 71 ]. Transcriptomic and spatiotemporal expression characteristic analysis in Freesia indicated that the expression patterns of selected WRKY and AP2 TF genes were consistent with flavonoid accumulation in the petals, suggesting their involvement in the regulation of flavonoid metabolism [ 72 ]. In our study, a total of five WRKY genes were identified in the brown module, one in the pink module, and three in the yellow module.…”
Section: Discussionmentioning
confidence: 99%
“…UV-B exposure led to the down-regulation of two bZIPs, and to the up-regulation of seven bZIPs in D. cambodiana (Figure 6), indicating that bZIPs may be those DEGs in the dragon tree responding to the UV-B challenge and regulating the production of flavonoids in dragon's blood. WRKY genes are also regulators of flavonoid accumulation in cotton [103], Freesia hybrida [104], Camellia sinensis [105], and so on. Some genes from flavonoid biosynthesis were regulated by OsWRKY89 in rice [106].…”
Section: Transcription Factors Involved In Secondary Metabolism Synth...mentioning
confidence: 99%